# Solve for y y=8(S-10)^2-16

y=8(S-10)2-16
Simplify each term.
Rewrite (S-10)2 as (S-10)(S-10).
y=8((S-10)(S-10))-16
Expand (S-10)(S-10) using the FOIL Method.
Apply the distributive property.
y=8(S(S-10)-10(S-10))-16
Apply the distributive property.
y=8(S⋅S+S⋅-10-10(S-10))-16
Apply the distributive property.
y=8(S⋅S+S⋅-10-10S-10⋅-10)-16
y=8(S⋅S+S⋅-10-10S-10⋅-10)-16
Simplify and combine like terms.
Simplify each term.
Multiply S by S.
y=8(S2+S⋅-10-10S-10⋅-10)-16
Move -10 to the left of S.
y=8(S2-10⋅S-10S-10⋅-10)-16
Multiply -10 by -10.
y=8(S2-10S-10S+100)-16
y=8(S2-10S-10S+100)-16
Subtract 10S from -10S.
y=8(S2-20S+100)-16
y=8(S2-20S+100)-16
Apply the distributive property.
y=8S2+8(-20S)+8⋅100-16
Simplify.
Multiply -20 by 8.
y=8S2-160S+8⋅100-16
Multiply 8 by 100.
y=8S2-160S+800-16
y=8S2-160S+800-16
y=8S2-160S+800-16
Subtract 16 from 800.
y=8S2-160S+784
Solve for y y=8(S-10)^2-16

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top